The effect of external credit on firms’ exports size in Nigeria - Richard Kofi Akoto (Taylor & Francis Group, 2021)
Financial market inadequacies often constrain overseas trade flows because exporters largely rely on access to external credit to survive. This article examines the influence of external credit (bank finance; and suppliers and customer credit) on exports size of manufacturing firms in Nigeria using Two-Stage Least Square (2SLS) estimation procedure. We approximate exports size as the ratio of exports over total sales. The study also proxy access to external finance as bank finance as a proportion of total financing while suppliers and customer credit was defined as credit from suppliers and advances from institutional customers as a proportion of total financing. The findings reveal that bank credit is significant and negatively associated with exports size while suppliers and customer credit are positive and significantly drives exports size. Government should put stringent measures in place to ensure that Nigeria’s exports meet overseas standards in terms of high-quality, packaging, and labeling, which are critical in selling exports in the international market. Policy should also be directed at reducing the cost of exporting in Nigeria. Finally, government should also consider establishing innovative tax incentives and credit guarantee schemes to encourage suppliers and institutional customers to extend more flexible credit to exporters.